(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
The Internet as a whole does not use secure links, thus information being transmitted may be vulnerable to interception as well. The importance of reducing the chances of information being detected during transmission is a major issue. A solution to be discussed is how passing of information can be done in a manner that the very existence of the message is unknown. This is important in order to repel attention from the potential attacker. Besides hiding data for confidentiality, this approach of information hiding can be extended to copyright protection of digital media. In this work, we focus on the achievement of a multi-layered security system by combining both cryptography and steganography. Encryption avoids passive attacks (reading) and by steganography, the message becomes undetectable. We make use of AES algorithm and Least Significant Bit (LSB) technique for hiding messages in an image. We have enhanced the LSB technique by randomly dispersing the bits of the message in the image and thus making it harder for an unauthorized person to extract the original message. The AES provides a good security as it takes considerably much more time to break by the brute force method for a given key length. The proposed methodology is proved good and produced expected output.